Engraftment, Fate, and Function of HoxB8-Conditional Neutrophil Progenitors in the Unconditioned Murine Host - Cohen, Joshua T.; Danise, Michael; Hinman, Kristina D.; Neumann, Brittany M.; Johnson, Renita; Wilson, Zachary S.; Chorzalska, Anna; Dubielecka, Patrycja M.; Lefort, Craig T. (Frontiers in Cell and Developmental Biology, 2022)
The development and use of murine myeloid progenitor cell lines that are conditionally immortalized through expression of HoxB8 has provided a valuable tool for studies of neutrophil biology. Recent work has extended the utility of HoxB8-conditional progenitors to the in vivo setting via their transplantation into irradiated mice. Here, we describe the isolation of HoxB8-conditional progenitor cell lines that are unique in their ability to engraft in the naïve host in the absence of conditioning of the hematopoietic niche. Our results indicate that HoxB8-conditional progenitors engraft in a β1 integrin-dependent manner and transiently generate donor-derived mature neutrophils. Furthermore, we show that neutrophils derived in vivo from transplanted HoxB8-conditional progenitors are mobilized to the periphery and recruited to sites of inflammation in a manner that depends on the C-X-C chemokine receptor 2 and β2 integrins, the same mechanisms that have been described for recruitment of endogenous primary neutrophils. Together, our studies advance the understanding of HoxB8-conditional neutrophil progenitors and describe an innovative tool that, by virtue of its ability to engraft in the naïve host, will facilitate mechanistic in vivo experimentation on neutrophils.